2024
DOI: 10.1002/jcp.31293
|View full text |Cite
|
Sign up to set email alerts
|

Ablation of Sam50 is associated with fragmentation and alterations in metabolism in murine and human myotubes

Bryanna Shao,
Mason Killion,
Ashton Oliver
et al.

Abstract: The sorting and assembly machinery (SAM) Complex is responsible for assembling β‐barrel proteins in the mitochondrial membrane. Comprising three subunits, Sam35, Sam37, and Sam50, the SAM complex connects the inner and outer mitochondrial membranes by interacting with the mitochondrial contact site and cristae organizing system complex. Sam50, in particular, stabilizes the mitochondrial intermembrane space bridging (MIB) complex, which is crucial for protein transport, respiratory chain complex assembly, and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 82 publications
0
4
0
Order By: Relevance
“…Previously, we have performed a rigorous 3D analysis of mitochondrial structure and networking in Sam50 -deficient human and murine myotubes, showing that the deletion of Sam50 results in smaller and less complex mitochondria (52). To further investigate SAM50’s role in mitochondrial structure, we knocked out Sam50 in fibroblasts and used mito-mCherry confocal to investigate structure (Figures 5N-O’’).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Previously, we have performed a rigorous 3D analysis of mitochondrial structure and networking in Sam50 -deficient human and murine myotubes, showing that the deletion of Sam50 results in smaller and less complex mitochondria (52). To further investigate SAM50’s role in mitochondrial structure, we knocked out Sam50 in fibroblasts and used mito-mCherry confocal to investigate structure (Figures 5N-O’’).…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we found that Sam50 is responsible for establishing and maintaining mitochondrial integrity, cristae structure, and mitochondrial metabolism (52). To identify the clinical implications of dysregulated SAMM50 gene expression in humans, we modeled genetically regulated gene expression (GReX) of SAMM50 across 85,615 individuals in the Vanderbilt biobank, BioVU (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations